Chapter 5: Offenses Against the Person, undated, reprinted in The Revised Ordinances Of Provo City, Containing All The Ordinances In Force 105-07, § 182 (1877) - (:unkn) unknown (My University, 1877)
Prohibited carrying a pistol, or other firearm, slungshot, false knuckles, Bowie knife, dagger or any other "dangerous or deadly weapon." Punishable by fine up to $25.
Keywords: CARRY